Cerebral microvascular density, blood-brain barrier permeability, and support for neuroinflammation indicate early aging in a Marfan syndrome mouse model - Curry-Koski, Tala; Curtin, Liam P.; Esfandiarei, Mitra; Thomas, Theresa Currier (Frontiers in Physiology, 2025)
IntroductionMarfan Syndrome (MFS) is a connective tissue disorder due to mutations in fibrillin-1 (Fbn1), where a Fbn1 missense mutation (Fbn1C1039G/+) can result in systemic increases in the bioavailability and signaling of transforming growth factor-β (TGF-β). In a well-established mouse model of MFS (Fbn1C1041G/+), pre-mature aging of the aortic wall and the progression of aortic root aneurysm are observed by 6-month-of-age. TGF-β signaling has been implicated in cerebrovascular dysfunction, loss of blood-brain barrier (BBB) integrity, and age-related neuroinflammation. We have reported that pre-mature vascular aging in MFS mice could extend to cerebrovasculature, where peak blood flow velocity in the posterior cerebral artery (PCA) of 6-month-old (6M) MFS mice was reduced, similarly to 12-month-old (12M) control mice. Case studies of MFS patients have documented neurovascular manifestations, including intracranial aneurysms, stroke, arterial tortuosity, as well as headaches and migraines, with reported incidences of pain and chronic fatigue. Despite these significant clinical observations, investigation into cerebrovascular dysfunction and neuropathology in MFS remains limited.MethodsUsing 6M-control (C57BL/6) and 6M-MFS (Fbn1C1041G/+) and healthy 12M-control male and female mice, we test the hypothesis that abnormal Fbn1 protein expression is associated with altered cerebral microvascular density, BBB permeability, and neuroinflammation in the PCA-perfused hippocampus, all indicative of a pre-mature aging brain phenotype. Glut1 immunostaining was used to quantify microvascular density, IgG staining to assess BBB permeability, and microglial counts to evaluate neuroinflammation.ResultsUsing Glut1 staining, 6M-MFS mice and 12M-CTRL similarly present decreased microvascular density in the dentate gyrus (DG), cornu ammonis 1 (CA1), and cornu ammonis 3 (CA3) regions of the hippocampus. 6M-MFS mice exhibit increased BBB permeability in the DG and CA3 as evident by Immunoglobulin G (IgG) staining. No differences were detected between 6M and 12M-CTRL mice. 6M-MFS mice show a higher number of microglia in the hippocampus compared to age-matched control mice, a pattern resembling that of 12M-CTRL mice.DiscussionThis study represents the first known investigation into neuropathology in a mouse model of MFS and indicates that the pathophysiology underlying MFS leads to a systemic pre-mature aging phenotype. This study is crucial for identifying and understanding MFS-associated neurovascular and neurological abnormalities, underscoring the need for research aimed at improving the quality of life and managing pre-mature aging symptoms in MFS and related connective tissue disorders.